The Study of Compacting Older Non-Open Neighborhoods based on Child-Friendly Concepts - Wei, Yao; Li, Hanchen; Ren, Xun; Wang, Hao (Transactions on Social Science, Education and Humanities Research, 2023)
This paper explores the pivotal role of robust interpersonal relationships among community residents in fostering the development of child-friendly communities. Drawing on extensive literature, including empirical studies conducted in diverse urban settings such as Changsha, Izmir, and rural communities in Uganda, this research underscores the transformative potential of strong community ties in enhancing the quality of life for children in urban environments. The study found the significance of community networks and social cohesion in creating environments conducive to the holistic development of children. These networks, characterized by high levels of social capital and mutual trust, facilitate the dissemination of crucial health information, promote participatory planning processes, and contribute to the realization of child-friendly urban design and infrastructure. The paper delves into the mechanisms through which well-connected communities can overcome the challenges posed by urbanization and industrialization, such as the erosion of traditional neighborhood relationships and the commodification of interactions, to construct harmonious and supportive environments for children. The findings of this research have profound implications for urban planning and policy formulation, emphasizing the need for a paradigm shift towards more inclusive and child-centered urban development strategies.